Effectiveness of Sugarcane Bagasse Adsorbent Combined with Aquaponics System as an Innovation for Absorbing Contaminants in Sugar Industry Wastewater - Hifdzil Adila; Wiliam Wisnu; Essa Tri Handayani; Hafizhah Rana Fathin; Andrew Setiawan Rusdianto (International Journal on Food, Agriculture and Natural Resources, 2023)
The sugar industry in its production produces by-products in the form of bagasse and liquid waste, both of which, if allowed to exist, can damage the ecosystem and the life of aquatic biota. Sugarcane bagasse contains cellulose which can be an adsorbent to reduce pollution in rivers. Apart from that, kale plants have the ability to release H ions which can reduce pollution by attracting heavy metal ions. The aim of this research is to determine the effectiveness of adsorbents from sugar cane bagasse in combination with aquaponics to reduce river pollution from liquid waste from the sugar industry. The research method used in this study was a completely randomized design with 2 factorials, namely the amount of adsorbent and the length of contact time of the adsorbent. The results of the research that has been carried out are obtained, the pH value is 6, the ammonia value is 0 mg/L, the TSS value is 150 mg/L, the DO value is 4.9 ppm, the BOD value is336 mg/L and the COD value is 254 mg/L. The conclusion of this research is that the combination of sugarcane bagasse adsorbent and an aquaponic system has been proven to reduce the concentration of pollutants in river water pollution caused by sugar industry wastewater.